Exploring Women’s Entrepreneurial Leadership and Digital Gamification Marketing in Fashion MSMEs - Ariasih, Made Putri; Sumadi Putra, Komang Endrawan; Suarmanayasa, I Nengah; Santi, Ni Wayan Ayu (Journal of Business and Economics Research (JBE), 2025)
This study explores the role of women’s entrepreneurial leadership and digital gamification marketing in enhancing the business performance of fashion MSMEs in Bali, Indonesia. Using a qualitative phenomenological approach, data were collected through in-depth interviews, direct observations, and document reviews involving selected women entrepreneurs in Bali’s fashion MSME sector who have successfully implemented both leadership and digital gamification strategies. The snowball sampling technique was applied to identify participants who met specific criteria related to entrepreneurial leadership and digital innovation practices. The findings reveal that women’s entrepreneurial leadership, characterized by empathy, inclusiveness, and collaboration, fosters creativity, innovation, and employee motivation, contributing to organizational growth. Gamification in digital marketing, such as point-based rewards, challenges, and social media engagement, enhances customer loyalty and purchase intention. However, MSMEs face challenges such as limited budgets, technological capacity, and maintaining creative consistency. The synergy between leadership and gamification forms a sustainable model leadership drives innovation and engagement, while gamification strengthens customer relationships and brand loyalty. Although the study emphasizes non-financial outcomes, including financial indicators such as profitability or revenue growth would enrich future analyses of business performance.